Pemeriksaan Kadar Glukosa Darah dan Status Kesehatan Body Mass Index (BMI) dalam Mendukung Gerakan Masyarakat Hidup Sehat (Germas) di Banjar Piakan, Desa Sibangkaja, Badung - Aryasa, I Wayan Tanjung; Artini, Ni Putu Rahayu; Apriyanthi, Desak Putu Risky Vidika; W, Ayu Saka Laksmita; Widayanti, Ni Putu; Iriani, Yulidia (Universitas Nusantara PGRI Kediri, 2025)
Nutrition is one of the problems for developing countries like Indonesia, the problem of nutrition becomes a double burden, namely underweight and overweight. Nutritional problems can increase the risk of low BMI disorders such as hypoglycemia, hypotension, and even malnutrition. While disorders that can be caused by high BMI can be obesity, hypercholesterolemia, and even coronary heart disease, the check can be carried out with free Community Service carried out by the Medical Lab Technology Study Program, Bali International University targeting the Banjar Piakan community, Sibang Kaja Village, Badung. The (POCT) method is used in checking blood glucose levels. The results of residents of Banjar Piakan, Sibangkaja Village, Badung who have a BMI <18.5 there are 3 people with 4.0% in the less than ideal category. BMI 18.5-24.9 of 23 people has a percentage of 31.08% in the ideal category, 13 people have more bb with a percentage of 31.08%, and residents who have a BMI with an obese category are 35 residents with a percentage of 47.29%. Based on blood glucose level parameters, residents of Banjar Piakan, Sibangkaja Village showed normal glucose levels of 55 residents of Banjar Piakan, Sibang kaja Village or 74.32% and only 19 people or 25.67% had glucose levels above 140 mg/dL. It can be concluded from this community service activity regarding checking BMI and even blood glucose can be used in examining health conditions.